Simulation of thermal comfort and energy demand in buildings of sub-Himalayan eastern India - Impact of climate change at mid (2050) and distant (2080) future. (1st June 2023) - Thapa, Samar; Rijal, Hom Bahadur; Pasut, Wilmer; Singh, Ramkishore; Indraganti, Madhavi; Bansal, Ajay Kumar; Panda, Goutam Kumar
Abstract: The global warming associated with climate change predicted by the Intergovernmental Panel on Climate Change (IPCC) is expected to deteriorate the indoor climate of free-running buildings. Features like proper orientation and wall thickness are important for the design of a building that is resilient to the impact of climate change. However, the implementation of these features is sometimes difficult, especially in a rugged hilly location. A whole building simulation was performed using DesignBuilder for an existing 3-storey free running multi-family concrete building located in the sub-Himalayan region of eastern India, for thermal comfort and energy demand during the present and the climate change scenarios of 2050 and 2080. The results show an increasing trend in the indoor operative temperature during the future climatic scenario, with the condition inside the top roof-exposed floor deteriorating the most. A decrease of 59.8% and 81.2% in the annual heating energy and an increase of 221.9% and 467.0% in the annual cooling energy were predicted for the future climate of 2050 and 2080 compared to the present. Parametric analysis performed considering orientation, wall U-value, infiltration rate and window-to-wall ratios revealed that the east/south-east facing orientation would perform the best with regard to overheating due to climate change. Further, the use of autoclaved aerated concrete (AAC) brick is recommended along with the decrease in air infiltration rate and window-to-wall ratio to improve the thermal performance of the indoor environment. In addition, we have also proposed a method to assess the under-cooling of an indoor environment. Highlights: Investigated the impact of climate change on indoor environment in cold climate Validated model of an existing 3-storey multi-family free running concrete building Proposed a method to assess the under-cooling of indoor environment Found increasing trend in indoor operative temperature with future climate Decrease in annual heating energy and increase in cooling energy demand observed